DAVID BURNS’ TEAM CBT THERAPY AS A TOOL FOR EDUCATIONAL COUNSELORS: Received: 02nd March 2021; Revised: 18th July 2021, 23rd August 2021; Accepted: 28th September 2021 - Bar Shalom, Yehuda; Specter, Amy (PUPIL: International Journal of Teaching, Education and Learning, 2021)
In this short article, the authors present their views on the effectiveness of Dr. David Burns’ TEAM therapy as an effective tool for educational counsellors in school settings. The authors are Yehuda Bar Shalom, who is both an academic who works in training counsellors and an educational counsellor in the field, draws from his experience as a TEAM therapist and trainer, and Amy Specter, who is a licensed marriage and family therapist who works at a high school for at-risk youth and also has a private practice working with teens and adults online in California. This paper should be seen as a practice-oriented account of two reflective practitioners.